2012
DOI: 10.1073/pnas.1205858109
|View full text |Cite
|
Sign up to set email alerts
|

Brain conditioning is instrumental for successful microglia reconstitution following hematopoietic stem cell transplantation

Abstract: The recent hypothesis that postnatal microglia are maintained independently of circulating monocytes by local precursors that colonize the brain before birth has relevant implications for the treatment of various neurological diseases, including lysosomal storage disorders (LSDs), for which hematopoietic cell transplantation (HCT) is applied to repopulate the recipient myeloid compartment, including microglia, with cells expressing the defective functional hydrolase. By studying wild-type and LSD mice at diver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
187
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(208 citation statements)
references
References 28 publications
15
187
0
Order By: Relevance
“…To assess tumorigenic potential, DIV 4-induced TH-GFP + cells were FACS sorted, replated, and transplanted the following day into 3-weekold immunodeficient Rag2 -/-Ilrg tmWjl -null mice, a strain that efficiently supports xenograft survival with particular sensitivity to rare tumorigenic cells (41). At 5 and 12 weeks after transplantation of about 5 × 10 5 iDA neurons (n = 10), we tested the integration and proliferation of the grafted cells.…”
Section: Resultsmentioning
confidence: 99%
“…To assess tumorigenic potential, DIV 4-induced TH-GFP + cells were FACS sorted, replated, and transplanted the following day into 3-weekold immunodeficient Rag2 -/-Ilrg tmWjl -null mice, a strain that efficiently supports xenograft survival with particular sensitivity to rare tumorigenic cells (41). At 5 and 12 weeks after transplantation of about 5 × 10 5 iDA neurons (n = 10), we tested the integration and proliferation of the grafted cells.…”
Section: Resultsmentioning
confidence: 99%
“…First, parameters such as morphology or CD45 expression may change with disease or injury. Second, chimeric mouse generation leads to partial chimerism, causes inflammatory damage, and can take many months (8,9). More recently, tools based on microglial expression of the fractalkine receptor, Cx3cr1, overcame some of these limitations.…”
mentioning
confidence: 99%
“…Consistently, Capotondo et al demonstrated that hematopoietic stem cell transplantation in a non-disease state of the host mice resulted in a short-term of cell infiltration into the brain. However, ablation of brain-resident myeloid precursors via busulfan treatment caused the long-term turnover of CNS microglia by the engrafted bone marrow-derived cells [114]. Following kainic acid administration with BU and cyclophosphamide treatment, circulating monocytes physiologically engrafted the brain and gave rise to activated macrophages [115].…”
Section: Pathological Conditions and Chemotherapies Induce The Infiltmentioning
confidence: 99%